2021
DOI: 10.37349/etat.2021.00064
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics comparison between maytansinoid-based and auristatin-based antibody-drug conjugates

Abstract: Aim: Direct analytical comparison of two major drug-linkers in the antibody-drug conjugate (ADC) field was conducted. Methods: Four different analytical methods [AlogP calculation, reverse phase (RP) high-performance liquid chromatography (HPLC; RP-HPLC), size exclusion chromatography HPLC (SEC-HPLC), and differential scanning calorimetry (DSC)] were tested for this comparison. Results: Maytansinoid-based ADCs showed less hydrophobicity than auristatin-based ADCs. Regardless of the drug-linker and drug-to-anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…The resulting GlycoConnect™ ADCs obtained from trastuzumab- 1 / 3 conjugated to 4 or from brentuximab- 1 / 3 conjugated to 5 were assessed head-to-head for in vitro stability with regards to aggregation (pH 5, 40°C). The enhanced aggregation levels of DAR4 ADCs based on 5 (red lines in Figure 4b ) versus the DAR2 ADCs based 4 (blue lines) were expected, 27 given the two-fold higher number of lipophilic payloads. However, it was surprisingly found that under these forcing conditions both ADCs obtained by remodeling with azidosugar 6-azidoGalNAc ( 3 ) showed reduced aggregation versus analogues ADCs remodeled with GalNAz ( 1 ), irrespective of whether they were conjugated to 4 or 5 .…”
Section: Resultsmentioning
confidence: 71%
“…The resulting GlycoConnect™ ADCs obtained from trastuzumab- 1 / 3 conjugated to 4 or from brentuximab- 1 / 3 conjugated to 5 were assessed head-to-head for in vitro stability with regards to aggregation (pH 5, 40°C). The enhanced aggregation levels of DAR4 ADCs based on 5 (red lines in Figure 4b ) versus the DAR2 ADCs based 4 (blue lines) were expected, 27 given the two-fold higher number of lipophilic payloads. However, it was surprisingly found that under these forcing conditions both ADCs obtained by remodeling with azidosugar 6-azidoGalNAc ( 3 ) showed reduced aggregation versus analogues ADCs remodeled with GalNAz ( 1 ), irrespective of whether they were conjugated to 4 or 5 .…”
Section: Resultsmentioning
confidence: 71%
“…ADCs produced using MTG‐mediated conjugation showed significant stability in mouse serum, and in vitro cytotoxicity and xenograft studies showed that these ADCs were sufficiently efficacious. Furthermore, thermal stability studies using differential scanning calorimetry [74] showed very similar values between the ADC and native mAb, alleviating previous concerns that the pharmaceutical development of transglutaminase/nonglycosylated mAb conjugates was not feasible due to low thermal stability.…”
Section: Transglutaminase‐mediated Modificationsmentioning
confidence: 58%
“…2C). Several previous studies, including ours, had reported stability assessments results of T-DM1 in peer-reviewed literature; and we followed the same procedures for one of the processes applied to trastuzumab-AJICAP-maytansinoid [13,[16][17][18].…”
Section: Gram-scale Preparation and Analysis Of Trastuzumab-ajicap-ma...mentioning
confidence: 99%
“…To adapt the AJI-CAP method of conjugation, a cysteine-reactive maytansinoid (MCC-maytansinoid, Fig. 1) was synthesized as previously reported [16]. The stability of trastuzumab-AJICAPmaytansinoid was assessed to determine its appropriate storage conditions [17,18].…”
Section: Introductionmentioning
confidence: 99%